2020
DOI: 10.3390/v12080861
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Candidates against Coronavirus Infections. Where Does COVID-19 Stand?

Abstract: Seven years after the Middle East respiratory syndrome (MERS) outbreak, a new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) made its first appearance in a food market in Wuhan, China, drawing an entirely new course to our lives. As the virus belongs to the same genus of MERS and SARS, researchers have been trying to draw lessons from previous outbreaks to find a potential cure. Although there were five Phase I human vaccine trials against SARS and MERS, the lack of data in humans provided us wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 84 publications
1
53
0
1
Order By: Relevance
“…Antibody-based treatments are also being investigated as potential drug candidates [ 3 , 4 ]. Additionally, there are numerous clinical trials in progress for potential vaccines of various platforms, ranging from DNA vaccines to inactivated virus vaccines [ 4 , 5 ]. With no signs of the virus slowing to date, there is an urgent need to develop vaccines, novel drug therapies and new strategies to combat this and future pandemics due to coronaviruses.…”
Section: Introductionmentioning
confidence: 99%
“…Antibody-based treatments are also being investigated as potential drug candidates [ 3 , 4 ]. Additionally, there are numerous clinical trials in progress for potential vaccines of various platforms, ranging from DNA vaccines to inactivated virus vaccines [ 4 , 5 ]. With no signs of the virus slowing to date, there is an urgent need to develop vaccines, novel drug therapies and new strategies to combat this and future pandemics due to coronaviruses.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to consider our results in the context of the ongoing COVID-19 pandemic, given the rapid and parallel development of dozens of vaccines against SARS-CoV-2 [25][26][27]. While many COVID-19 vaccines in development target the same spike protein, some target epitopes in other genes [26] and the potential for multi-epitope (i.e., cocktail) vaccines is being investigated (e.g., [28][29][30][31]).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to consider our results in the context of the ongoing COVID-19 pandemic, given the rapid and parallel development of dozens of vaccines against SARS-CoV-2 [25][26][27]. While many COVID-19 vaccines in development target the same spike protein, some target epitopes in other genes [26] and the potential for multi-epitope (i.e., cocktail) vaccines is being investigated (e.g., [28][29][30][31]). If in the future multiple COVID-19 vaccines were approved with similar efficacies (i.e., roughly equal protection against the predominant circulating strain), then our results suggest that to minimize the risk of evolutionary escape and reduce the total number of individuals who get infected, the vaccines should be used in a mosaic strategy (sensu [13]).…”
Section: Discussionmentioning
confidence: 99%
“…Data from several eagerly awaited randomised clinical trials will determine how BCG affects COVID-19 infection. The BCG-CORONA (the Netherlands) and BRACE (Australia) placebo-controlled trials are studying the effects of BCG on 1500 and 10.078 healthcare workers, respectively exposed to COVID-19 patients [15][16][17] . Additionally, a study in the USA reported a statistically significant reduction in the number of COVID-19 disease related to hospital admissions in BCG-vaccinated participants (although the authors did not indicate when they were vaccinated) 18 .This suggests that BCG vaccination deployment may reduce COVID-19 cases, hospitalisations, and deaths, a view shared by many opinion leaders.…”
Section: Epidemiological and Clinical Evidence Of Bcg-mediated Protecmentioning
confidence: 99%